Barbados. Significant achievements 2014 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Barbados during 2014 are identified, with respect to the needs and interests of the country, strengthening issues such as innovation, safety, horticulture, poultry farming, organic agriculture, permaculture, leadership, nutrition, permaculture and forty vegetables. Likewise, work was done on drip irrigation, agricultural health, risk management, water management, rabies control and resilience against climate change. Finally, the improvement of sheep production was supported in partnerships between the public and private sectors, in standards and legislation.